Forecasting Cash Use in Legal and Illegal Activities - David B. Humphrey; Aris Kaloudis; Grete Øwre (Norges Bank, 2000)
A general econometric model is developed and used to estimate the share of cash in consumer point-of-sale transactions in Norway over 1980-99. The share of cash fell from 90% during the 1980s to 50% in 1999, primarily due to debit card growth. Additional data from banks, stores, and elsewhere give an estimate of the total use of cash in legal activities. The stock of cash that is unaccounted for is an estimate of cash used in illegal activities. This totals 10% of GDP and has risen by 63% over 5 years. Projections of future cash use are also made.
hdl:11250/2500392
Keywords: E41; H26; 330; cash; money; tax evasion